Natural Resource Conflict and Resolution Practice in Nepal (RR Interdisciplinary Journal, 2023)
Natural resource conflict and management practices in Nepal have been significant due to the diverse geographical and ecological features as well as socio-economic complexities. Nepal is home to a wide range of natural resources which often become a source of dispute among different stakeholders. The paper explores the conflict associated to Natural resources which covers classes of interest group, disagreements, public protests, physical assaults, and the filing of cases in courts. It has been prepared by collecting data from primary and secondary sources when unstructured observation, focus group discussion and interview with respondent were conducted for primary data and books, journals were used for secondary data. The Balakhu village was selected purposively to study of condition, use pattern of natural resource in the village. Differences between rules and behavior, social relations, and the incompatibility of goals, actions and interactions framed in their specific context and time would be considered in analyzing resource conflict. Such conflict can be resolved by using formal practice of rule and regulation or law and using informal practice of traditional methods.